Selective Laser Melting of Titanium Alloys and Titanium Matrix Composites for Biomedical Applications: A Review1 . Issue 4 (6th October 2015) - Zhang, Lai‐Chang; Attar, Hooyar
Abstract : Titanium materials are ideal targets for selective laser melting (SLM), because they are expensive and difficult to machinery using traditional technologies. After briefly introducing the SLM process and processing factors involved, this paper reviews the recent progresses in SLM of titanium alloys and their composites for biomedical applications, especially developing new titanium powder for SLM. Although the current feedstock titanium powder for SLM is limited to CP‐Ti, Ti–6Al–4V, and Ti–6Al–7Nb, this review extends attractive progresses in the SLM of all types of titanium, composites, and porous structures including Ti–24Nb–4Zr–8Sn and Ti–TiB/TiC composites with focus on the manufacture by SLM and resulting unique microstructure and properties (mechanical, wear/corrosion resistance properties). Abstract : Titanium materials are ideal targets for selective laser melting (SLM), because they are expensive and difficult to machinery, using traditional technologies. This review extends attractive progresses in SLM of all types of titanium, their composites and porous structures, with focus on the manufacture by SLM and the resulting microstructure and properties and the development of new alloy powder materials. The SLM process and factors involved are also briefly reviewed.